Majestie - Teems, David; Nang Chan Yeema (Nashville, TN USA Thomas Nelson, 2010)
Offers an engaging new look at the world's most cherished, revered, and influential translation of Sacred Writ and the king behind it.
Keywords: Adult Nonfiction